Sustainability Competencies: analysis in a Financial Institution (Research, Society and Development, 2019)
This paper addresses the theme of competencies for sustainability when considering the concern with sustainability in the business environment under the social, environmental and economic perspectives. We investigate competences in the context of sustainability, considering the competence of systemic thinking; the competence of anticipation; normative competence; strategic competence and interpersonal competence in a financial institution. The main objective was to analyze the strategies and competencies focused on the organizational sustainability of Banco Alfa in the State of Paraná. This is a descriptive research, with a quantitative approach and a single case study. The survey was made available through the SurveyMonkey® online survey platform for the 8,636 employees of the State of Paraná, resulting in 1,042 valid effective respondents. Interviews were conducted with 4 bank unit managers as a way of supporting quantitative data, besides the documentary analysis. The results showed that there is a significant relationship between the time of the company, the commission and the age group. The study contributed in practice, because it was possible to understand how the competencies for sustainability are perceived by the employees and managers of the financial institution and the strategic actions that could be developed for this.